2002
DOI: 10.1080/1024242021000032494
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Modification of Paper Fibres

Abstract: The enzymatic mode of action in paper fibre upgrading is still uncertain. In an attempt to clarify how enzymes modify pulp and paper properties, several parameters were analysed in the present work: (i) thermal analysis of the water -solid surface interactions; (ii) fibre cake permeability; (iii) particle size analysis. The results obtained suggest that enzymes modify the interfacial properties of fibres, increasing the water affinity, which in turn change the technical properties of pulp and paper, such as dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Such a treatment was also tested on Simao pine bleached kraft pulp [17], hardwood kraft pulp [15,18] or bamboo pulp [19,20] and induced some potential savings in beating. This was consistent with observation from Pala et al [21] who suggested that enzymes modified the surface properties of fibres, increasing the water affinity.…”
Section: Introductionsupporting
confidence: 92%
“…Such a treatment was also tested on Simao pine bleached kraft pulp [17], hardwood kraft pulp [15,18] or bamboo pulp [19,20] and induced some potential savings in beating. This was consistent with observation from Pala et al [21] who suggested that enzymes modified the surface properties of fibres, increasing the water affinity.…”
Section: Introductionsupporting
confidence: 92%
“…XRD patterns were obtained using Cu Kα radiation, a diffraction angle 2 θ from 10° to 30° (step size of 0.02°) and a counting time of 2 s. The CrI was calculated using the equation CrI [%] = ( I 002 - I AM )/ I 002 × 100, where I 002 is the maximum intensity of the crystalline plane (002) reflection (2 θ = 22.5°) and I AM is the intensity of the scattering for the amorphous component at about 18° in cellulose-I [36]. Different CrI values for Sigmacell 101 can be found in the literature [37,38]. This may be explained by the varying quality of cellulose depending on batches and production location [39].…”
Section: Methodsmentioning
confidence: 99%
“…The recycling of paper is an area where the use of enzymes has been implemented, seeing that the recycled fibres' properties can be improved by treatment with cellulases and hemicellulases. In fact, these enzymes modify the interfacial properties of fibres, increasing the affinity for water, which in turn promotes changes in the technical properties of the pulp and paper, such as pulp drainability and paper strength [1][2][3]. These enzymes are also used for upgrading secondary fibres' deinking [4].…”
Section: Introductionmentioning
confidence: 98%